Принципи побудови системи органів державного управління землею - Бусуйок, Д.В. (Правова держава: Щорічник наукових праць, 2010)
У статті досліджуються питання організації системи органів державного управління земельним фондом. Визначаються вади функціонування сучасної системи органів державного управління землею. З метою їх усунення пропонуються принципи побудови сучасної системи органів державного управління землею. В статье исследуются вопросы организации системы органов государственного управления земельным фондом. Определяются недостатки функционирования современной системы органов государственного управления землей. С целью их устранения предлагаются принципы построения современной системы органов государственного управления землей. The questions of organ’s system organization of state administration the land fund are being studied in the article. The defects of the functioning of the modern organ’s system organization of state administration the land fund are being determined. The principles of construction of the modern organ’s system organization of state administration the land fund are being offered with the purpose of the defects removal.